THE IMPACT OF HUMAN RESOURCE MANAGEMENT ON ORGANIZATIONAL PERFORMANCE: PROGRESS AND PROSPECTS - Waqar Akbar Khan; Yang Minghai; Muhammad Nadim; Dr. Abida Hafeez; Kellala Massinissa; Dr. Maja Pucelj (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
This study examines the impact of human resource management (HRM) practices on organizational performance. The target population consists of employees working in various organizations. A structured questionnaire was developed and distributed to all members of this population. The aim of this research is to explore the strategies implemented by HRM and their influence on organizational performance. The insights provided by employees in this industry are crucial for answering the research questions. The sample size for this study was 300 respondents, selected using a nonprobability sampling technique. Random sampling was employed as the sampling method. The data collection and research methodologies adhered to ethical guidelines. The questionnaire was distributed among the employees to gather relevant data for analysis. By investigating the relationship between HRM practices and organizational performance, this study aims to contribute to the existing body of knowledge in the field. The findings from this research provide insights and recommendations for organizations to enhance their HRM practices and ultimately improve their performance outcomes.